Peremajaan Merek Melalui Redesign Logo Usaha & Kemasan Wajit Cililin - Tintin Suhaeni; Ivon Sandya Sari Putri; Ira Siti Sarah; Abdul Malik Sayuti; Maya Setiawardani; Sri Raharso; Harmon Chaniago (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2021)
Intense competition, uncertain market conditions, and social and lifestyle factors are often the reasons why a brand must always keep up with the times, either by changing some aspects of the brand partially or totally. Brands that experience stagnation or even losses have to be decided whether to be dismissed or retained. If the choice is maintained, then brand rejuvenation can be an alternative. Brand rejuvenation is an attempt to bring a brand that can’t make money into money-making with new positioning. Our partners, Wajit Cililin craftsman, have started their business decades ago. Since the business was founded, not many changes and innovations have been made in terms of supply so that partners are currently experiencing a phase of stagnation in their business. For this reason, the team offers a solution, namely a brand rejuvenation assistance program. The output of this program, in addition to the report, is also in the form of a scientific article, a scientific poster, and registration of intellectual property rights in the form of partners’ brands. Specifically, this program will produce logo and packaging designs for partners, to the point that the packaging is ready to use according to the design plan. The program consisted of a series of activities begins with a pre-survey to see the latest conditions of partners, personal interviews with potential partners to raise priority needs for which solutions will be made, literature studies to enrich to theoretical foundations of packaging design, surveys to get the preference of consumers, packaging design, packaging production process and evaluation of consumer perceptions of the logo and packaging that has been made.